Motives For Adopting A Green Economy To Achieve Sustainable Development In Some Arab Countries - زيود, لين; لؤي صيوح ,; عبير ناعسه, (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The research aimed to shed light on the nature of the green economy, and to explain its relationship with sustainable development, while highlighting the experiences of some Arab countries in it, as well as identifying the motives and justifications for adopting the green economy, and indicating the extent to which it is necessary to be adopted by the state when it embarks on achieving sustainable development. Research on the available data in reports published by specialized international organizations on some Arab countries. The researcher reached a number of results, the most important of which are: The green economy is an integral part of sustainable development, as it represents the environmental dimension of it, and it is assumed that they should be implemented in parallel. There is a set of objective motives and justifications in the Arab world that encourage the establishment and development of green projects. Green economy projects are considered a solution to a group of environmental problems in the Arab world. • The lack of oil and gas in some Arab countries, such as Morocco, is a catalyst for the development and diversification of green projects.